Visual Cryptography for Image Processing and Security Theory, Methods, and Applications - Liu, Feng; Yan, Wei Qi (Springer International Publishing : Imprint: Springer, 2015)
This unique text/reference addresses the fundamental concepts in the theory and practice of visual cryptography, a secret sharing technique which allows the encryption of an image without requiring any complex computation or knowledge of cryptography. The design, construction, analysis, and application of visual cryptography schemes (VCSs) are discussed in detail. Original, cutting-edge research is presented on probabilistic, size invariant, threshold, concolorous, and cheating immune VCS. This updated second edition has also been expanded with new content on braille and 2D barcode authentication of visual cryptography shares. Topics and features: • Contains review exercises at the end of each chapter, as well as a helpful glossary (NEW) • Provides a thorough introduction to the field of visual cryptography • Examines various common problems in visual cryptography, including the alignment, flipping, cheating, distortion, and thin line problems • Reviews a range of visual cryptography schemes, including XOR-based visual cryptography and security enriched VCS • Describes different methods for presenting color content using visual cryptographic techniques • Covers such applications of visual cryptography as watermarking, resolution variant VCS, and multiple resolution VCS This logically-structured and comprehensive work will serve as a helpful reference for all researchers and students interested in do.